2013
DOI: 10.1111/nure.12079
|View full text |Cite
|
Sign up to set email alerts
|

2′-fucosyllactose: an abundant, genetically determined soluble glycan present in human milk

Abstract: Lactose is the preeminent soluble glycan in milk and a significant source of energy for most newborn mammals. Elongation of lactose with additional monosaccharides gives rise to a varied repertoire of free soluble glycans such as 2'-fucosyllactose (2'-FL), which is the most abundant oligosaccharide in human milk. In infants, 2'-FL is resistant to digestion and reaches the colon where it is partially fermented, behaving as soluble prebiotic fiber. Evidence also suggests that portions of small soluble milk glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 158 publications
(441 reference statements)
4
110
0
4
Order By: Relevance
“…Propanediol is produced by gut microbes as a fermentation byproduct of rhamnose and fucose (Badia et al 1985). These simple sugars are components of glycoconjugates found in intestinal epithelial cells and plant cell walls (Bry et al 1996), as well as in breast milk oligosaccharides (Castanys-Munoz et al 2013). Sriramulu et al (2008) have shown that DSM 20016 (clade II) shows a growth advantage over rodent-derived L. reuteri 100-23 (that lacks the pdu – cbi – hem – cob cluster) when propanediol is provided in the growth medium, further supporting the idea that clade II strains preferentially utilize the propanediol dehydratase activity of PduCDE.…”
Section: Resultsmentioning
confidence: 99%
“…Propanediol is produced by gut microbes as a fermentation byproduct of rhamnose and fucose (Badia et al 1985). These simple sugars are components of glycoconjugates found in intestinal epithelial cells and plant cell walls (Bry et al 1996), as well as in breast milk oligosaccharides (Castanys-Munoz et al 2013). Sriramulu et al (2008) have shown that DSM 20016 (clade II) shows a growth advantage over rodent-derived L. reuteri 100-23 (that lacks the pdu – cbi – hem – cob cluster) when propanediol is provided in the growth medium, further supporting the idea that clade II strains preferentially utilize the propanediol dehydratase activity of PduCDE.…”
Section: Resultsmentioning
confidence: 99%
“…HMOs have been postulated as key ingredients for brain development due to their high abundance and variety in maternal milk when compared to bovine-milk based formulas [31]. Fucosylated HMOs are predominant in breast milk, especially 2’-FL which is the most abundant HMO, in most women’s milk [32]; while oligosaccharides from cow’s milk are mainly sialylated, and are present at low levels. Our group we reported the first in vivo study of dietary HMOs on CNS function, whereby 2´-FL potentiated LTP evoked at the hippocampus, improved learning and memory skills and impacted several brain markers of synaptic plasticity and brain function in rodents [17].…”
Section: Discussionmentioning
confidence: 99%
“…HMOs have been postulated as key ingredients for brain development due to their high abundance and variety in maternal milk when compared to bovine-milk based formulas [37]. In particular, 2'-FL is the most abundant HMO in most women's milk [38], while oligosaccharides from cow's milk are mainly sialylated, and are present at low levels. Thus, dissecting a role for 2'-FL in cognitive development is of great interest.…”
Section: Accepted Manuscriptmentioning
confidence: 99%